Attitudes of Students and Teachers Towards Using Technology in Cooperative Learning Activities in ESL Classes - Mostafa, Shorouk (2021)
The current study aims to explore the attitudes of high school students and their teachers towards using technology in cooperative learning activities during ESL classes. For this purpose, the TAM model was used to design surveys to explore the stakeholders’ attitudes. The study is conducted in an American school in the UAE, and the researcher adopted a quantitative method that involves two weeks of technology intervention in a cooperative learning setting. A survey is distributed to teachers and students to explore their attitudes. The findings suggest that most teachers and students have positive opinions about integrating technology into ESL cooperative learning activities.